2022
DOI: 10.1101/2022.03.23.485451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis defines a broader FMRFamide-gated sodium channel family and determinants of neuropeptide sensitivity

Abstract: FMRFamide and similar neuropeptides are important physiological modulators in most invertebrates, but the molecular basis of FMRFamide activity at its receptors is unknown. We therefore sought to identify the molecular determinants of FMRFamide potency in one of its native targets, the excitatory FMRFamide-gated sodium channel (FaNaC) from gastropod mollusks. Using molecular phylogenetics and electrophysiological measurement of function, we identified a broad FaNaC family that includes mollusk and annelid chan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Interestingly, all these described channels form a sister clade with a group of early diverging homologues from cnidarians and the poriferan species Sycon ciliatum. A distinct group of channels within the ENaC superclade contains the FMRFamide and Wamide neuropeptide-gated sodium channels (i.e., FaNaC and WaNaC channels), recently shown to be conserved between the lophotrochozoan lineages of molluscs and annelids (9). These form a sister clade relationship with several channels from the phoronid Phoronis australis and M.lignano.…”
Section: Running Title: a Trichoplax H + -Gated Deg/enac Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, all these described channels form a sister clade with a group of early diverging homologues from cnidarians and the poriferan species Sycon ciliatum. A distinct group of channels within the ENaC superclade contains the FMRFamide and Wamide neuropeptide-gated sodium channels (i.e., FaNaC and WaNaC channels), recently shown to be conserved between the lophotrochozoan lineages of molluscs and annelids (9). These form a sister clade relationship with several channels from the phoronid Phoronis australis and M.lignano.…”
Section: Running Title: a Trichoplax H + -Gated Deg/enac Channelmentioning
confidence: 99%
“…Nonetheless, during evolution these channels underwent extensive sequence divergence and genetic expansion/loss in different animal lineages, in several cases obscuring their phylogenetic relationships. Although several recent phylogenetic studies have provided some important insights (8)(9)(10), there are still many unanswered questions about the evolutionary origins ASIC, BASIC, and ENaC channels, and their relationships with the many divergent channels identified in invertebrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, Cottrell and colleagues identified FMRFamide (Phe-Met-Arg-Phe-amide)-gated ion channels in the snail, Helix aspersa (Cottrell et al 1990). Subsequent investigation identified an entire family of FMRF-amide-gated channels in Hydra, the HyNaCs (Assmann et al 2014;Dürrnagel et al 2012;Golubovic et al 2007), as well as additional amidated peptide-gated sodium channels (FaNaCs) from molluscs and annelid channels, gated by FMRFamide, FVRIamides and Wamides (Dandamudi et al 2022;Lingueglia et al 1995;Schmidt et al 2018). Despite extensive screening (Vyvers et al 2018), no native peptide agonist for mammalian ASICs has yet been identified, but several are known to potentiate acid-induced currents.…”
Section: Neuropeptides and Toxins: Channel Modulation And Therapeutic...mentioning
confidence: 99%